Assessing the Assignment Policy for Army Women - Harrell, Margaret C. (RAND Corporation, 2007)
Since current policies for assigning military women were issued, the U.S. Army has changed how it organizes and fights. Assessing the Assignment Policy for Army Women considers whether the Army is adhering to the assignment policies as well as the appropriateness of the current U.S. Department of Defense and Army assignment policies, given how units are operating in Iraq.